English-language gifted students' attitudes towards project-based approach to learning writing - Nguyễn, Thị Thu Huyền (University of Languages and International Studies, 2017)
Definitions of Writing. The importance of writing. Approaches to teaching writing. Definitions of project-based learning. Advantages and disadvantages of Project-based Learning.